Azulene in Polymers and Their Properties - Zeng, Hui Ning; Png, Zhuang Mao; Xu, Jianwei (Chemistry, an Asian journal, 2020)
Azulene, a unique isomer of naphthalene, has received much interest from researchers in different fields due to its unusual chemical structure with a negatively charged 5‐membered ring fused with a positively charged 7‐membered ring. In particular, incorporation of azulene into polymers has led to many interesting properties. This minireview covers functionalization methods of azulene at its various positions of 5‐ and 7‐membered rings to form azulene derivatives including azulene monomers, and gives an overview of a wide range of azulene‐containing polymers including poly(1,3‐azulene), azulene‐based copolymers with connectivity at 1,3‐positions of the 5‐membered ring, or 4,7‐positions of the 7‐membered ring, as well as copolymers with azulene units as side chains. Their chemical and physical properties together with applications of azulene‐containing polymers have also been summarized. This minireview summarizes the latest development of a range of azulene‐containing polymers, highlighting 1,3‐connected polyazulene, 1,3‐connected, 4,7‐connected and 2,6‐connected azulene‐containing copolymers with a special emphasis on the polymer synthesis as well as their electrical and optical properties.